A study on the factors that influence the sales performance of Ableace (M) Sdn Bhd towards international market / Nik Norsuhana Radzali - Radzali, Nik Norsuhana (Faculty of Business and Management, 2009)
Ableace (M) Sdn. Bhd (AAM) was set up in 1997 as one of the trading and manufacturing of oleo chemicals and palm oil products in Malaysia. From its early days as local exporter in 1997, AAM charted a growth path and expands the business by setup a group consist Ableace Industries Sdn bhd (AAI) established in 2002, Ableace Assets Sdn Bhd (AAA) in 2005 and Ableace Raakin Sdn Bhd formed in 2006. Its evolution as a group with a strength financial performance in Malaysia leads on expanding footprint in Asia and elsewhere. AAM is focused on being a recognized leader in all its markets, delivering exceptional value to its customers and achieving sustainable growth in both local and international Markets. Even though the achievement of AAM look excellent on the paper actually is not going well for the AAM as a group. It was the reason why the researcher does for this research study. The main objective for this research is to identify or to find the factors that influence sales performance of AAM. For the purpose of this dissertation, the qualitative research was used; the researcher used an interview method as a tool to get the information from the AAM staff. This research also used secondary data as a tool for getting the information about AAM especially on sales matters. From this research, it can be concluding that the most factors influence for the AAM performance internally and externally. Also, we can see the trend for the new sales performance for the AAM.